Collaborative knowledge creation : practices, tools, concepts - Moen, Anne; Mørch, Anders; Paavola, Sami (Technology-enhanced learning, 2012)
This book presents perspectives on the knowledge creation metaphor of learning, and elaborates the trialogical approach to learning. The knowledge creation metaphor differs from both the acquisition and the participation metaphors. In a nutshell trialogical approaches seek to engage learners in joint work with shared objects and artefacts mediated by collaboration technology. The theoretical underpinnings stem from different origins, including Bereiter and Scardamalia's theory on knowledge building and Engeström's activity theory. The authors in this collection introduce key concepts and techniques, explain tools designed and developed to support knowledge creation, and report results from case studies in specific contexts. The book chapters integrate theoretical, methodological, empirical and technological research, to elaborate the empirical findings and to explain the design of the knowledge creation tools. The target audiences for this book are researchers, teachers and Human Resource developers interested in new perspectives on collaborative learning, technology-mediated knowledge creation, and applications of this in their own settings, for higher education, teacher training and workplace learning. The book is the result of joint efforts from many contributors who took part in the Knowledge-practices Laboratory (KP-Lab) project (2006-2011) supported by EU FP6.